Exploring the Impact of Cryptocurrency on Terrorism - Akcinaroglu, Seden (Terrorism and political violence, 2025)
The nexus between economic motivations and terrorist activities has been extensively theorized, but existing explanations often overlook the contemporary shifts in terrorist financing ushered in by technological advancements. The advent of cryptocurrencies, with their hallmarks of anonymity, decentralization, liquidity, usability, and profitability, has bestowed upon terrorist groups new avenues for raising funds while remaining largely clandestine. This exploratory research delves into the repercussions of this digital financial realm, examining how Bitcoin popularity, price volatility, and regulatory frameworks influence the operational latitude of terrorist groups. Drawing on the Global Terrorism Database (GTD) for terrorist attack data, coupled with Google Trends data on “bitcoin” searches from 2009 to 2020 as an indicator of cryptocurrency popularity in each country, the study uncovers a nuanced dynamic. While the rising prominence of cryptocurrencies subtly amplifies the operational sphere for terrorist outfits, the uncertain nature of Bitcoin prices as well as the legal and regulatory landscape act as deterrents.